If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x = 6x + 35 Reorder the terms: 11x = 35 + 6x Solving 11x = 35 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 11x + -6x = 35 + 6x + -6x Combine like terms: 11x + -6x = 5x 5x = 35 + 6x + -6x Combine like terms: 6x + -6x = 0 5x = 35 + 0 5x = 35 Divide each side by '5'. x = 7 Simplifying x = 7
| 7x=2x+45 | | 3(m-4)-(m+2)=0 | | 6(4x-7)=12 | | 6x^2+12x+4=0 | | 2(7x+2)=2x | | 3+3m+1=2m+4+m | | 7(8x-5)=21 | | 5n(12-2n)= | | n+12=20 | | 11x=5x+36 | | 10y(6xy-14)= | | 9x=7x+18 | | 4+n=-2 | | 7+n=40 | | 24x^2-8x=0 | | 7(5x-7)=28 | | 2(3x-7)=4 | | m=3/5 | | 11x=8x+12 | | 2(6x+5)=8x | | (3x+4)+(2x-1)= | | 6x=2x+36 | | 9x+3x+12=0 | | 14x^2+13x+3= | | (3x+4)+(5x+2)= | | 12+(-8)= | | 5x^2+10x+20=0 | | (5x+5)+(3x-3)= | | 2(w+1)+4w=3(2w-1)+8 | | -4(v+2)+2=2(v+6) | | 5x^2=13x-12 | | 45=3x |